2008
DOI: 10.1111/j.1463-5224.2008.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of medetomidine hydrochloride on the electroretinogram of normal dogs

Abstract: Medetomidine significantly prolongs the implicit time and lowers the amplitude response of both the a- and b-waves in normal dogs at all flash intensities examined. Clinically, however, medetomidine only minimally affects the retinal responses and is a viable choice for use in dog ERGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 36 publications
1
32
0
3
Order By: Relevance
“…The combination of xylazine and butorphanol in this study, provided a good sedation and allowed adequate recording and low noise interference. No alterations were observed on ERG results due to the sedation protocol, as it may be observed when conducted with barbiturate or inhalation anesthetic agents (Norman 2008, Ekesten et al 2012.…”
Section: Discussionmentioning
confidence: 92%
“…The combination of xylazine and butorphanol in this study, provided a good sedation and allowed adequate recording and low noise interference. No alterations were observed on ERG results due to the sedation protocol, as it may be observed when conducted with barbiturate or inhalation anesthetic agents (Norman 2008, Ekesten et al 2012.…”
Section: Discussionmentioning
confidence: 92%
“…There are many variables that can influence the ERG recordings, which could be divided into two categories: physiological and instrument-related factors. While the purpose of this report is not to review those factors, physiological factors include body temperature [60] and those introduced by the protocol such as pupillary dilation [3], and the anaesthetic agent used [26,[61][62][63]. It has been recently demonstrated that injected propofol slightly influences ERG parameters during the transient injection time only [62].…”
Section: Erg and Anaesthesiamentioning
confidence: 98%
“…Em virtude da presença de muitas variáveis, como método de registro, estímulo, adaptação ao escuro, protocolo de sedação ou anestesia que podem alterar os resultados do ERG, é indicado que cada laboratório tenha seus parâmetros de normalidade (MENTZER et al, 2006;NORMAN et al, 2008). Objetivou-se, com este estudo, padronizar os valores de normalidade da resposta de bastonetes, máxima resposta e resposta de cones em cães da raça Poodle portadores de catarata madura ou hipermadura, de acordo com a faixa etária, utilizando aparelho portátil BPM 200.…”
Section: Eletrorretinograma (Erg) é Um Meio Diagnóstico Objetivo Nãounclassified